Istirātījiyyatu Ta‘līmi Mahārati al-Kalāmi fī Firqati Rā’idati al-Lughati al-‘Arabiyyati bi Jāmi‘ati al-Amien Prenduan - Uswatun Hasanah; Umul Mulyatun (KURAS Institute, 2025)
To create an effective classroom atmosphere, teachers must implement active and enjoyable learning strategies so that the learning process does not become boring for the students. The strategy for teaching speaking skills is a method used in the learning process to help students develop their Arabic speaking skills effectively. The objectives of this research are to identify the strategies used in teaching speaking skills in the Arabic Language Excellence Class at Al-Amien Prenduan University, as well as to examine the inhibiting and supporting factors in the process of teaching speaking skills in the same class. The researcher employed a qualitative research method, while the data were collected through observation, interviews, and documentation. The data analysis techniques used included data condensation, data display, and conclusion drawing. To ensure the validity of the data, the researcher applied source triangulation. The findings of this research indicate that there are several strategies for teaching speaking skills applied by the teachers in the Arabic Language Excellence Class at Al-Amien Prenduan University, namely: training students to be confident in delivering presentations, creating a supportive classroom atmosphere, presenting materials in an attractive and enjoyable way, using instructional media, and giving rewards. Furthermore, in the implementation of these strategies, several inhibiting factors were identified, including students’ lack of self-confidence, limited application of vocabulary, and school absence. Meanwhile, the supporting factors include the existence of an Arabic-speaking environment in daily activities, the presence of regulations that require speaking Arabic, and the availability of competent teachers.